2002
DOI: 10.1007/s004240100718
|View full text |Cite
|
Sign up to set email alerts
|

Influence of systemic treatment with cyclooxygenase inhibitors on lipopolysaccharide-induced fever and circulating levels of cytokines and cortisol in guinea-pigs

Abstract: Peripheral inflammatory stimuli result in the modification of a number of vital brain-controlled functions including the thermoregulatory set-point (induction of fever) and the activity of the hypothalamic-pituitary-adrenal (HPA) axis. We addressed the question of whether both of these components of the acute-phase response are induced by a common signal pathway. For this purpose we recorded body temperature (by remote radio-telemetry), HPA axis activity (circulating concentrations of cortisol by radio-immunoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 45 publications
0
25
1
2
Order By: Relevance
“…Another potential limitation might be a certain heterogeneity between the animals of the 2 series. Since diclofenac induces also dose-dependent fluctuations of systemic cytokine levels, we should point out that the reported effects of diclofenac are also heterogeneous [19,20,21,22]. This was particularly well documented for TNF-α levels where elevation is described after diclofenac treatment but is partially abolished in a dosage of 3 mg/kg body weight s.c. [23].…”
Section: Discussionmentioning
confidence: 95%
“…Another potential limitation might be a certain heterogeneity between the animals of the 2 series. Since diclofenac induces also dose-dependent fluctuations of systemic cytokine levels, we should point out that the reported effects of diclofenac are also heterogeneous [19,20,21,22]. This was particularly well documented for TNF-α levels where elevation is described after diclofenac treatment but is partially abolished in a dosage of 3 mg/kg body weight s.c. [23].…”
Section: Discussionmentioning
confidence: 95%
“…The increase in CSF PGE 2 probably reflects the induction of COX-2 in the brain capillary endothelial cells where LPS or cytokines transiently enhance COX-2 mRNA and protein levels (31). COX-2 mRNA expression in brain capillary cells is enhanced as early as 1 h after peripheral LPS administration (100 g/kg ip) (6), which is compatible with the development of anorexia and other LPS-induced effects, such as fever and activation of the hypothalamic-pituitary-adrenal axis (35), which are also reported to be mediated by COX-2 and CNS PGs.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of the role of COX-1 and COX-2 in LPS fever were done mainly in mice and guinea pigs (Li et al, 1999;Steiner et al, 2001;Roth et al, 2002). However, most work on brain mechanisms of fever were done in rats, and we wanted data comparable to our previous detailed studies of the fever curve and brain Fos responses in i.v.…”
Section: Technical Considerationsmentioning
confidence: 90%
“…COX-1 -/-mice showed typical fevers during the first 2 hours after administration of low dose LPS, but COX-2 -/-mice developed hypothermia (Li et al, 1999). Pretreatment of guinea pigs with a COX-1 inhibitor (SC-560) in a similar model did not affect febrile responses to low doses of LPS, but a COX-2 inhibitor (nimesulide or meloxicam) attenuated the fever (Steiner et al, 2001;Roth et al, 2002). Cao et al (1997) found that a COX-2 inhibitor prevented fever in rats after intraperitoneal LPS, but did not examine the effect of a COX-1 inhibitor.…”
mentioning
confidence: 92%